2021
DOI: 10.15240/tul/001/2021-2-003
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Intellectual Capital and Its Impact on Business Sustainability: Evidence from Small, Medium, and Large Enterprises

Abstract: The main goal of this article is to analyze the level of differentiation of awareness and knowledge among managers of small, medium and large enterprises in the scope of the essence and meaning of intellectual capital as well as the influence of its elements on the sustainable development of enterprises in Poland. Intellectual capital is perceived as a key resource of an enterprise. It is also one of the most valuable resources of an enterprise, which enables its sustainable development. It is critical base of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Employees would not be motivated to get involved in achieving the results set by the leader and, consequently, it would not be possible to fulfil the made assumptions in full (Moszoro, 2011;Wilmanowicz, 2012). Above all, it is for this reason that it is necessary to jointly create a vision, according to which the company operates in the spirit of sustainable development, and to enable subordinates to actively participate in the implementation of the strategy and the systematic evaluation of its results, thus adopting a participative style of management, where participation and participation are among the employee motivation tools (Gross--Gołacka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Employees would not be motivated to get involved in achieving the results set by the leader and, consequently, it would not be possible to fulfil the made assumptions in full (Moszoro, 2011;Wilmanowicz, 2012). Above all, it is for this reason that it is necessary to jointly create a vision, according to which the company operates in the spirit of sustainable development, and to enable subordinates to actively participate in the implementation of the strategy and the systematic evaluation of its results, thus adopting a participative style of management, where participation and participation are among the employee motivation tools (Gross--Gołacka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With the added concepts of spiritual capital [7] and the intangible assets of enterprises, enterprise intellectual capital was put forward as a concept in business management [8]. Moreover, the coexistence and influence of different intellectual capital elements are considered important for the sustainable development of enterprises [9].…”
Section: Literature Review 21 Intellectual Capitalmentioning
confidence: 99%
“…This is in line with the resource base value (RBV) as our theoretical framework. Several empirical studies have demonstrated that intellectual capital is a strategic asset and significantly affects organizational performance in various fields and perspectives, including universities (Anggraini et al, 2018b(Anggraini et al, , 2018aBrusca et al, 2019;Pedro et al, 2022), banking (Castro et al, 2021;Chahal & Bakshi, 2016;Pernamasari & Sugiyanto, 2021), manufacturing (Rosario & Mazumdar, 2022;Subagyo & Waluyo, 2020;Tsai & Mutuc, 2020;Xu & Liu, 2020), and entrepreneurship (Al-Jinini et al, 2019;Arshad et al, 2014;Demartini & Beretta, 2020;Gross-Gołacka et al, 2021). Furthermore, prior studies have explored the critical role of IC in the hospitality tourism industry (Aboushouk & Tamamm, 2021;Bontis et al, 2015;Kim et al, 2012;Rudež, 2021;Zeglat & Zigan, 2013).…”
Section: Introductionmentioning
confidence: 99%